A produção científica docente nos programas de pós-graduação em Ciência da Informação no Brasil: um estudo bibliométrico - Osorio, Hevelyn de Paula [UNESP] (2012)
For the construction of scientific knowledge in different areas, including in the context of Information Science, scientific and academic productions are basic elements to be considered. Therefore, this study proposed to analyze the scientific production of Information Science post-graduation professors (Universidade Federal de Minas Gerais, Universidade de Brasília, Universidade Estadual Paulista and Universidade de São Paulo) with concept 5 in CAPES ranking during the period of 2007 to 2009, intending to check the visibility of their scientific production. More specifically, we sought to identify the most productive authors of books, book chapters, articles and conference proceedings, the kinds of authorship contained in these publications, as well as the most common themes. We conducted a survey of the journals in which the university published, and the stratum Qualis, besides the participation of professors in national and international events. The search procedure took place from the survey of publications of professors in 28 books, 251 book chapters, 651 papers in conference proceedings and articles located in section 354 Indicators of CAPES. Through the variables, a network of professors’ co-authorships, institutional collaboration network, and the network that establishes the relationship between subject and teachers using the software Pajek were built up. Results show that there is not a preferential channel for the dissemination of research from professors of Information Science post-graduation programs, but there is a greater frequency of publications in conference proceedings, mainly national. Professors from the Information Science programs perform more collaboration among researchers from the same institutions, and institutional collaboration network revealed that there is little dialogue between the four Information Science post-graduation programs researched. In summary, it was...